GROWTH PERFORMANCE OF OREOCHROMIS NILOTICUS NILOTICUS (LINNAEUS) WITH RESTRICTED FEEDING - PEGU, RITUPARNA; DAS, SUDHIR KUMAR (Journal of the Inland Fisheries Society of India, 2021)
The compensatory growth for Oreochromis niloticus niloticus (Linnaeus) was studied through restricted feeding regime. The fishes in 3 treatments groups were fed @ 2 percent body of weight for the period 1 week, 2 weeks and 3 weeks respectively. Subsequently fishes were fed at the rate of 5 percent of body weight till 9 week. The fishes in control (C) group were fed daily @ 5 percent of body weight. There was significance difference (df = 3.8, F = 7.574, P < 0.05)) in weight gain of fish due to feed restriction. It was found that in the treatment R2 there was relatively high growth during 4th and 5th week and it might be due to hyperphagia in fish. It had also resulted in growth compensation.Key words: Restricted feeding, Compensatory growth, Oreochromis niloticus niloticus